ROLE OF THE EMOTIONS AND CLASSROOM ENVIRONMENT IN WILLINGNESS TO COMMUNICATE: APPLYING DOUBLY LATENT MULTILEVEL ANALYSIS IN SECOND LANGUAGE ACQUISITION RESEARCH. Issue 3 (2nd November 2017) - Khajavy, Gholam Hassan; MacIntyre, Peter D.; Barabadi, Elyas
Abstract: The purpose of the present study was to examine the relations between emotions, classroom environment, and willingness to communicate (WTC) using the advanced quantitative methodological procedure of doubly latent multilevel analysis. To this end, 1528 secondary school students from 65 different classrooms in Iran participated in the study. Results of the doubly latent multilevel analysis showed that a positive classroom environment is related to fostering WTC and enjoyment, while it reduces anxiety among students. Moreover, enjoyment was found as an important factor in increasing WTC at both student and classroom level, while anxiety reduced WTC only at the student level. Finally, the results of the study are discussed and pedagogical implications are provided for language teachers.